Extração de polissacarídeos do caroço de açaí (Euterpe oleracea) - Freitas, Danieli Melo de (Universidade Federal de São Carlos, 2011)
The development of the productive chain of agribusiness açaí depends on the proper disposal of by-products generated. The fruit is used currently only the mesocarp for human consumption, creating an environmental problem, since the core represents approximately 75-81% of the total weight of the fruit. The stone of açaí literature reports the presence of inulin, polyphenols and other carbohydrates. Among these inulin stands out for its low calorie and therefore applied in food production light in fat or low fat, as a substitute for fat and sugar. Despite being distributed worldwide, is not produced in Brazil and its imports makes it a product of high cost. Thus the design goal was to develop a method for extraction of inulin on a laboratory scale, aiming its industrial production. In the first stage of the project was undertaken to adapt the methodology for aqueous extraction of açai and the core of analytical methods for quantification of compounds. In the second stage of the project was carried out an experimental design to evaluate the effect of variables in the process of extracting the content of polysaccharides: temperature, particle size of the lump, mass / volume ratio and stirring speed of the mixture. In the third step, through the hydrolysis and HPLC analysis, was not found the polysaccharide inulin. By NMR analysis and infrared is proposed that this polysaccharide is a galactomannan. The content of the core polysaccharide, soluble in water, ranged 2-7%. The insoluble fraction of the core, obtained by extracting basic, representing 15% of the total mass.
Keywords: Biotecnologia; Polissacarídeos; Carboidratos; Resíduos; Açaí; Polysaccharide; Residue; CIENCIAS BIOLOGICAS::BIOQUIMICA